Answer:
B. y+ 4 = 3/4 (x-6)
Step-by-step explanation:
Given:
m = 3/4
Slope-intercept:
y - y1 = m(x - x1)
y + 4 = 3/4(x - 6)
Answer:
<h2>
2x + 3y = 33 </h2>
Step-by-step explanation:
As we move from (-2, 5) to (1, 3), x increases by 3 and y decreases by 2.
Hence, the slope of this line is m = rise / run = -2/3.
Start with the slope-intercept form y = mx + b.
Substitute 3 for y and 1 for x and -2/3 for m:
3 = (-2/3)(1) + b.
Remove fractions by mult. all three terms by 3:
9 = -2 + b, so b = 11, and y = (-2/3)x + 11
Again, mult. all three terms by 3:
3y = -2x + 33, or, in standard form,
<h2>
2x + 3y = 33 </h2>